IbM UNTUK PENINGKATAN PRODUKTIVITAS PENGRAJIN TIKAR DI DESA GONDANGREJO KARANGANYAR - Harimurti, Fadjar (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
The service was done in Ngaglik and Pancuran villages, Gondangrejo, Karanganyar, Central Java. These areas have the potential to produce mats with semi traditional method. Most of the villagers are the matsâ weavers and worker of the weavers. The village has a potential in developing the craft of mats. The main problem from the craftsmen are the management, the production process is less than optimal, no efficiency in production process and the management of the marketing. In this service, many activities are held such as training in management and creativity, displaying of the technologyâs application, and marketing technique for the product. The result of this service with Ibm are the optimal production process and the handling of the marketing.Keywords: Mats, productivity, craftsmen, production